비대면 서비스 접점인 콜센터의 서비스 품질 차원과 고객만족과의 관계 - 서효영(Seo, Hyo-Young); 최수정(Choi, Su-Jeong); 정기주(Cheong, Ki-Ju) (대한경영학회지, 2013)
고객의 서비스에 대한 기대 및 요구가 지속적으로 증가하는 상황에서, 고객에게 우수한 서비스를 제공하는 것을 핵심 업무로 담당하는 서비스 접점의 역할이 강조되고 있다. 서비스 접점의 품질은 고객이 지각하는 기업의 서비스 품질을 의미한다. 즉, 고객은 서비스 점점에서의 경험을 통해 기업의 서비스에 대한 전반적인 평가를 형성한다. 우수한 서비스 품질은 고객을 만족시키고 충성도를 제고하여 궁극적으로 기업의 새로운 수익창출에도 기여할 수 있다. 그러므로 서비스 접점에서 제공하는 서비스 품질의 관리는 여전히 중요한 이슈로 남아 있다. 본 연구는 기업의 비대면 서비스 접점으로 급성장한 콜센터의 서비스 품질에 초점을 맞춘다. 기존의 면대면 서비스 접점을 대상으로 수행된 많은 연구들과는 달리 전화상으로 제한된 시간동안 고객서비스를 전달해야 하는 콜센터 서비스 상황에서, 고객은 면대면 서비스 품질을 평가했던 기존의 차원과는 다른 새로운 차원으로 서비스 품질을 평가할 것이다. 그러므로 본 연구는 Cronin과 Taylor(1992)의 SERVPERF 모형을 토대로 콜센터의 서비스 품질 차원들을 도출하고자 한다. 이에 덧붙여, 본 연구는 콜센터의 서비스 품질을 평가하는데 새롭게 추가해야 할 차원은 무엇인지 규명하고자 한다. 이를 위해, 정보시스템 및 콜센터 등의 비대면 서비스 환경에서 강조해 온 접근성의 개념을 서비스 연구에 접목시키고자 한다. 마지막으로, 본 연구는 도출된 서비스 차원들이 고객만족에 미치는 효과를 실증 분석하고자 한다. 콜센터에서의 서비스 경험을 보유한 이용자를 대상으로 수집된 164부의 응답을 본 연구의 분석에 이용하였다. 분석결과는 다음과 같다. 먼저, 콜센터의 서비스 품질 차원으로 접근성, 대응성, 확신성, 공감성의 네 가지 차원이 도출되었으며, 이들 차원들은 모두 고객만족에 유의한 영향을 미치는 것으로 나타났다. 이와 더불어, 본 연구에서 새롭게 제시한 품질 차원 변수인 접근성은 고객만족에 가장 큰 영향을 주는 것으로 밝혀졌다. 이 결과는 고객에게 콜센터로의 신속한 연결 제공, 상담사와의 연결과정에서 짧은 대기시간, 자동응답시스템의 편리한 설계 및 이용 용이성 제공, 자동응답시스템에서의 신속한 상담원 연결기능 제공 등의 접근성이 콜센터를 이용하는 고객의 만족을 증가시키는데 가장 중요한 부분임을 제시한다. With customers' expectations and demands of service increasing, service encounters have been emphasized as a typical customer contact point of a firm. Service encounters attempt to meet customers' such expectations and demands by offering superior service to customers. Customers form an overall impression on a firm's service quality based on service provided by service encounters. Previous studies have asserted that superior service determines customer satisfaction, thereby leading to customer loyalty. However, little has been known about major dimensions of service quality in the context of call centers. Customers may use different criteria in evaluating service quality provided by call centers. Compared with general face-to-face interaction, call centers deliver service automatic response systems(ARS) and/or service providers over the phone. In this regard, there is a need to identify new dimensions of service quality in call center settings. For this, we draw four dimensions from the SERVPERF model: reliability, responsiveness, assurance, and empathy. However, tangible dimension is excluded in that it is useful for measuring physical environments surrounding service. In addition, we draw an accessibility construct from IS literature as a new dimension for measuring service quality of call center. Accessibility can be considered as a useful construct to measure the extent to which customers easily, quickly search and use appropriate service via ARS, and they can interact with service providers when needed. Finally, we examine the effects of the dimensions of service quality on customer satisfaction. To test the hypotheses, we conducted a multi-regression analysis using data collected from 164 customers who have experience in call center service. The results indicated that accessibility has the most significant effect on customer satisfaction. Moreover, the results showed that responsiveness, assurance, and empathy are significant in enhancing customer satisfaction. Thus, accessibility should be considered as a major dimension in determining customers' satisfaction in the context of call centers. KCI Citation Count: 19